Separation and Determination of Poly Aromatic Hydrocarbons in Vegetables Samples in Baghdad City Using HPLC Technique - AbdulRada, Nawar J.; Hussain, Khalil I.; Ali, AbdulJabbar A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Reversed  Phase High Performance Liquid  Chromatography (RP-HPLC) has been used for the separation of  Poly aromatic hydrocarbons(PAHs) by using column Reprosil 100 C 18 which  was found to be a suitable one for this purpose. The result showed that using mobile phase of (Acetonitrile-water) Reversed Phase HPLC , flow rate  of (1.2 ml/min) , column temperature (30CËš) and wave length of (254nm), give a complete separation with a good resolution . The total separation time was less than 20 min. The result of the study showed that the vegetables of Baghdad city were   polluted by poly aromatic hydrocarbons(PAHs) in different places where samples taken because of drainage  of the heavy water ,industrial trash and trash of oil colanders. -Naphthalene, Acenaphthylene, Acenaphthene, Fluorene, Phenanthrene,  Anthracene, Fluoranthene, Benzo(g,h,i)perylene , Pyrene , Benzo(a)anthracene,  chrysene Benzo(a)Pyrene,Benzo(b)fluoranthene, Benzo(k)Fluoranthen   ,   Dibenzo(a,h)Anthracene,  and Indeno(1,2,3-cd)pyrene